2011
DOI: 10.1007/s10439-011-0397-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Tracking of a Patient’s Health Condition Based on Pulse Rate Dynamics During Sleep

Abstract: This article proposed a method to track the changes in health condition of a patient after coronary stenting over seven successive seasons based on daily pulse rate (PR). The pulse signal was recorded by an unconstrained monitoring system during sleep. Seasonal PR dynamics were evaluated by both linear measures, including time domain and frequency domain indexes, and nonlinear measures such as noise limit (NL), detection rate (DR), sample entropy (SampEn), and Poincaré plots. NL and DR were derived using the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In our earlier investigation (Chen et al, 2008, 2009a), we have compared heartbeat interval fitting point process models using different probability distributions, and found that the inverse Gaussian model achieved the overall best fitting results. In practice, we can always conduct an empirical model fit analysis (e.g., data histogram, the Q-Q plot, and the Kolmogorov-Smirnov plot) for the raw R-R intervals, testing the appropriateness of the inverse Gaussian model (Chen et al, 2011a). …”
Section: Methods and Datamentioning
confidence: 99%
See 4 more Smart Citations
“…In our earlier investigation (Chen et al, 2008, 2009a), we have compared heartbeat interval fitting point process models using different probability distributions, and found that the inverse Gaussian model achieved the overall best fitting results. In practice, we can always conduct an empirical model fit analysis (e.g., data histogram, the Q-Q plot, and the Kolmogorov-Smirnov plot) for the raw R-R intervals, testing the appropriateness of the inverse Gaussian model (Chen et al, 2011a). …”
Section: Methods and Datamentioning
confidence: 99%
“…In light of equation (8), the frequency response for the baroreflex (BP → RR) or RSA (RP → RR) is computed as (Chen et al, 2009a, 2011a)…”
Section: Methods and Datamentioning
confidence: 99%
See 3 more Smart Citations